A review of moisturizing additives for atopic dermatitis - Vanessa, Vincentsia Vienna; Wan Ahmad Kammal, Wan Syazween Lyana; Lai, Zee Wei; How, Kang Nien (MDPI, 2022)
Atopic dermatitis, the most common form of eczema, is a chronic, relapsing inflammatory skin condition that occurs with dry skin, persistent itching, and scaly lesions. This debilitating condition significantly compromises the patient’s quality of life due to the intractable itching and other associated factors such as disfigurement, sleeping disturbances, and social stigmatization from the visible lesions. The treatment mainstay of atopic dermatitis involves applying topical glucocorticosteroids and calcineurin inhibitors, combined with regular use of moisturizers. However, conventional treatments possess a certain degree of adverse effects, which raised concerns among the patients resulting in non-adherence to treatment. Hence, the modern use of moisturizers to improve barrier repair and function is of great value. One of the approaches includes incorporating bioactive ingredients with clinically proven therapeutic benefits into dermocosmetics emollient. The current evidence suggests that these dermocosmetics emollients aid in the improvement of the skin barrier and alleviate inflammation, pruritus and xerosis. We carried out a critical and comprehensive narrative review of the literature. Studies and trials focusing on moisturizers that include phytochemicals, natural moisturizing factors, essential fatty acids, endocannabinoids, and antioxidants were identified by searching electronic databases (PubMed and MEDLINE). We introduce the current knowledge on the roles of moisturizers in alleviating symptoms of atopic dermatitis. We then further summarize the science and rationale of the active ingredients in dermocosmetics and medical device emollients for treating atopic dermatitis. Finally, we highlight the limitations of the current evidence and future perspectives of cosmeceutical research on atopic dermatitis.